Odpowiedzi

2010-04-08T23:23:02+02:00
I)
sinαcosβ= ½[sin(α-β)+ sin(α+β)]
uzasadnienie:
korzystamy z wzorów:
1) sin(α+β)= sinαcosβ+ cosαsinβ
2) sin(α-β)= sinαcosβ- cosαsinβ
prawa strona= ½[sin(α-β)+ sin(α+β)]=
½[sinαcosβ- cosαsinβ+sinαcosβ+ cosαsinβ]=
½[2sinαcosβ]= sinαcosβ = lewa strona
II)
cosαsinβ= ½[sin(α+β)-sin(α-β)]
uzasadnienie:
korzystamy z wzorów:
1) sin(α+β)= sinαcosβ+ cosαsinβ
2) sin(α-β)= sinαcosβ- cosαsinβ
prawa strona= ½[sin(α+β)- sin(α-β)]=
½[sinαcosβ+ cosαsinβ- (sinαcosβ- cosαsinβ)]=
½[sinαcosβ+ cosαsinβ- sinαcosβ+ cosαsinβ]=
½[2cosαsinβ]= cosαsinβ= lewa strona